Human factor of information security - Poyda-Nosyk Nina; Пойда-Носик Ніна; Pojda-Noszik Nina; Kálmán Botond Géza; Malatyinszki Szilárd; Калман Ботонд Гейзо; Малатінскі Сілард; Malatyinszki S. (II. RFKMF, 2024)
Abstract. Nowadays, we live in an era of transformation, next to Industry 4.0 and globalization, and perhaps even ahead of them, sustainability has become of prime importance. The essence of this is to preserve our current level of development in such a way as to protect resources for future generations. In connection with sustainability, they often talk about sustainable development and even sustainable growth. However, this is an illusion [1], primarily because the material stock is finite and can never be renewed without loss.
Az információbiztonság emberi tényezője
Людський фактор інформаційної безпеки
Keywords: human factor; information security